Pengembangan Materi Teks Catatan Harian Dalam Bentuk Buku Suplemen Berbasis Pendekatan Pengalaman - Rofi’atul Mukaromah (CV. Gerasi Insan Nusantara, 2022)
Supplement book is a teaching material complement for student which from student’s text book. There are some extra material from the main teaching material based from student’s book. In addition, supplement book is also known as complement book of student’s text book. The supplement book has some developing of teaching material from student’s text book. The teaching material which has developed in this research is daily note text teaching material that was packed into supplement book. Dialy note book teaching material in supplement book has developed based on experience approachment with 4D developing (define, design, develop, and dessiminate). This developing model is suggested by Thiagarajan, Semmel, and Semmel that adapted into 3D (define, design, and develop). The result of this research show that Developing of dialy note text teaching material based on experience approachment in supplement book is deserved for the students based from the quality of content, language, presentation and also the graphic. The valuation for this research is based from the validator of language, content, and presentation, the validator of graphic, bahasa Indonesia teacher as monitoring teacher and also researche’s parteners. Beside that, the efectiveness is very effective based on the valuation from monitoring teacher and also researche’s partners when this methode was shown in the class